Potentiometric Ethene Sensor for Postharvest Detection Applications. Issue 15 (1st January 2019) - Sekhar, Praveen K.; Ludwig, Tim; Wilhelm, Michael; Graf, David; Riheen, Manjurul Ahsan; Mathur, Sanjay
Abstract : A sensitive and selective electrochemical sensor for the detection of ethene is reported. Reduced Graphene Oxide (rGO)-Copper (Cu) nanocomposite modified Lanthanum Strontium Chromite (LSC) and Pt are used as electrodes. Yttria-Stabilized Zirconia (YSZ) is used as the solid electrolyte. This bilayer electrochemical sensor was suitable for the detection of up to 10 parts per billion (ppb) of ethene that is of significant interest for post-harvest monitoring applications. The mixed potential sensor responded non-linearly to varying concentrations of Ethene (0 to 100 ppb). A 30% reduction in ethene sensor response was observed when the relative humidity was increased to 80% (from 10%). The optimal operating temperature of the sensor was found to be 500°C considering the sensitivity-response time trade-off. The device exhibited a strong interference rejection potential to NH3 and CO. The next generation of such a mixed potential sensor with integrated heaters and miniaturized implementation will enable the possibility of ethene sensor commercialization similar to the automotive oxygen sensor.